Effect of Microwave Drying on the Drying Characteristics, Color, Microstructure, and Thermal Properties of Trabzon Persimmon - Soner Çelen (Foods, 2019)
In this study, changes in the drying kinetics, color change, and the energy consumption for microwave energy were investigated for Trabzon persimmon. In addition to that, the microstructure of the persimmon was also investigated by considering its thermal changes. It is important to be aware of the purpose of the drying process for determining the drying system. Results of this research showed that 460 W for 7 mm slice thickness depending on energy consumption, 600 W for 5 mm slice thickness depending on drying time, and 600 W depending on color changes were found as suitable drying processes depending on drying conditions. The effective diffusion values varied between 2.97 × 10−8 m2 s−1 and 4.63 × 10−6 m2 s−1. The activation energy values for 5 mm, 7 mm and 9 mm slice thickness were estimated as 32.82, 18.64, and 12.80 W g−1, respectively. The drying time and energy consumption decreased, whereas drying rate increased with an increase in the microwave energy. The number of pores increased compared to structure of fresh sample, and the pores got to be larger for 5 mm slice thickness as the power level increased. Results showed that the applied microwave energy had an important effect on the heating of the material and the change in the microstructure.